Dobór optymalnej pojemności zbiornika retencjonującego wody w małych zlewniach deszczowych = Optimum required capacity of the tank in the small drainage basin - Pązik, Rafał; Kostecki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The capacity of the tank is an important factor affecting the efficiency of the drainage system. Its selection depends on the size of the rain and the water inflow to the tank. The purpose of this study was to determine the effect of improper selection of capacity of tanks in small urban catchments.
Keywords: zlewnia miejska; mały zbiornik retencyjny; urban catchment; small drainage tank